(3x^2-2Y^2)(9X^4+6X^2Y^2+4Y^4)
1个回答
(3x^2-2Y^2)(9X^4+6X^2Y^2+4Y^4)
=(3x²)³-(2y²)³
=27x^6-8y^6
相关问题
若x+2y=1,2x-3y=2,则2x+4y-6/2+6x-9y/4=?
1/(6X-4Y)-1/(6X+4Y)+3X/(4Y^2-9X^2)=
1.(x+4)(x-7)+10 2.1-6xy^3+9x^2y^6 3.(9x^2-4y^2)-(3x+2y) 4.(m
计算(2x+3y)(2x-3y)(9y2+4x2)-(4x2-9y2)2
(9x3y4-6x4y3+3x2y3)÷______=-3x2y2+2x3y-xy.
X∧4+4Y∧4X∧3-3X∧2-2X+216X∧2-9Y∧2+32X+16X∧4+X∧2Y∧2+Y∧4
1.(16y^4-9x^4)/(-3x^2-4y^2) 2.(-2x+y)(-2x-y)
(1)y=x^2-7x=6 (2)y=3x^4+4x^3 (3)y=x^3-x^2-4x+4 (4)y=2x^2-x^4
1.计算1/6x-4y +1/6x+4y — 3x/4y^2-9x^2
【4】(-2x+3y)(-2x-3y) 【5】(-1/4x-2y)(-1/4x+2y) 【6】x^2+(y-x)(y+x